The 3D Printing of Freestanding PLLA Thin Layers and Improving First Layer Consistency through the Introduction of Sacrificial PVA - David M. Roper; Kyung-Ah Kwon; Serena M. Best; Ruth E. Cameron (Applied Sciences, 2021)
Fused filament fabrication (FFF) is an inexpensive way of producing objects through a programmed layer-by-layer deposition. For multi-layer, macro-scaled prints, acceptable printing is achieved provided, amongst other factors, first layer adhesion is sufficient to fix a part to the surface during printing. However, in the deposition of structures with a single or few layers, first layer consistency is significantly more important and is an issue that has been previously overlooked. As layer-to-bed adhesion is prioritised in first layer printing, thin layer structures are difficult to remove without damage. The deposition of controllable thin structures has potential in tissue engineering through the use of bioactive filaments and incorporation of microfeatures into complex, patient-specific scaffolds. This paper presents techniques to progress the deposition of thin, reproducible structures. The linear thickness variation of 3D-printed single PVA and PLLA layers is presented as a function of extrusion factor and the programmed vertical distance moved by the nozzle between layers (the layer separation). A sacrificial PVA layer is shown to significantly improve first layer consistency, reducing the onus on fine printer calibration in the deposition of single layers. In this way, the linear variation in printed single PLLA layers with bed deviation is drastically reduced. Further, this technique is used to demonstrate the printing of freestanding thin layers of ~25 µm in thickness.